Advanced MoS2 nanocomposite materials for the synthesis of valuable pharmaceuticals. (2022) - Gaur, Rama; Mukherjee, Nandini; Shahabuddin, Syed; Chandra, Prakash
Abstract: Rampant industrialization has played pivotal role in generation of polluting materials threatening ecology, environment and biosphere reserves. Amongst various pollutants, nitroarmatics are key components of non-biodegradable organic dyes, insecticides having toxic and carcinogenic effect on human health. Furthermore, aromatic hydrocarbons are widespread contaminants of ground water. Therefore, these waste materials are generally degraded by advanced oxidation process to carbon dioxide and water. But, these organic waste materials instead of complete mineralization can be valorized to valuable pharmaceuticals. For example, nitroaromatics can be valorized to tertiary amine or N-Mannich bases. N-Mannich bases are important pharmacophores and used as anti-microbial, anti-viral, anti-HIV, anti-inflammatory, analgesics and RSK2 inhibitory. Ethylbenzene is an important industrial waste can be used as building block for the synthesis of α-ketoamides. These α-ketoamides are significant pharmacophores can be used as the broad-spectrum antibiotics for COVID-19. Presently, COVID-19 is a global pandemic affecting billions of people. To deliver doses to such a big population would be a challenge. Therefore, we can use the industrial waste materials for the synthesis of valuable pharmacophors to boost the economy. To effectively catalyze the transformation of these industrial wastes into valuable products, cost-effective, readily available catalytic materials will be investigated. Earth abundant transition metals like Cu, Co, Zn, Ni, Zr etc. supported over 2D transition metal dichalcogenides can be used as the desirable candidates for the synthesis of pharmacophors from industrial waste. These catalytic materials will be prepared by hydrothermal or reverse micelle microemusion technique form metal salts or metal dithiocarbamates based single source molecular precursors.